2020
DOI: 10.1002/ardp.202000298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiseizure effect evaluation of nonimidazole histamine H3receptor antagonists containing the oxazole moiety

Abstract: The use of histamine H3 receptor (H3R) antagonists is becoming a promising therapeutic approach for epilepsy. In this paper, a series of novel nonimidazole H3R antagonists was synthesized and screened as antiepileptic drugs. All of these prepared antagonists displayed micromolar or submicromolar H3R antagonistic activities in the cAMP response element luciferase screening assay. Compounds 5a (IC50 = 0.11 μM), 5b (IC50 = 0.56 μM), and 5f (IC50 = 0.78 μM) displayed the most potent H3R antagonistic activities, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…As previously described and with a slight modification in the intensity applied, seizures were elicited in mice with a 50-Hz alternating current of 120 mA intensity ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ). The current was applied through ear electrodes for 0.2 s. Protection against the spread of MES-induced convulsion was defined as the abolition of the tonic hind limb extension (THLE) component of the seizure ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described and with a slight modification in the intensity applied, seizures were elicited in mice with a 50-Hz alternating current of 120 mA intensity ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ). The current was applied through ear electrodes for 0.2 s. Protection against the spread of MES-induced convulsion was defined as the abolition of the tonic hind limb extension (THLE) component of the seizure ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described and with a slight modification in the intensity applied, seizures were elicited in mice with a 50-Hz alternating current of 120 mA intensity ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ). The current was applied through ear electrodes for 0.2 s. Protection against the spread of MES-induced convulsion was defined as the abolition of the tonic hind limb extension (THLE) component of the seizure ( Kaminski et al, 2015 ; Song et al, 2020 ; Xiao et al, 2021 ; Hua et al, 2023 ). The animals were divided into the following experimental groups, with eight mice in each: the control group injected with saline, the positive control group injected with 300 mg/kg of VPA (the minimal dose of VPA that protected animals against the spread of MES-induced convulsions without mortality in mice) ( Sadek et al, 2015 ; Bastaki et al, 2018 ), and four groups that were administered the test compound DL76 at doses of 7.5 mg/kg, 15 mg/kg, 30 mg/kg, or 60 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…One of the two test models is the MES seizure model, another is the PTZ-induced seizure model. In our previous work, we found that the synthetic H3R antagonists and PIT showed an antiseizure activity at 10 mg/kg [22]. In addition, the administration of this dosage can minimize the impact of other possible side effects such as central inhibition and cardiac toxicity.…”
Section: Evaluation Of the Antiseizure Activitymentioning
confidence: 97%
“…In our previous work, dozens of 2-methyl-4-phenyloxazoles were designed and synthesized as new H 3 R antagonists [22]. All these compounds showed micromolar to submicromolar H 3 R antagonistic activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of heterocyclic compounds designation, there has been a markedly increased interest in the invention of new heterocyclic compounds, especially nitrogen-bearing ones, because of their prevalence in nature and also in pharmacology. Piperidine moiety is a generative basis of numerous therapeutically important compounds due to its numerous biological and pharmacological activities 1,2 including anticancer 3–5 anti-proliferative compounds against MCF-7 breast cancer and PC-3 prostate, HepG2 cancer cells, 6 antidiabetic, 7 antidepressant, 8 H 3 R antagonistic, 9 antibacterial, 10 antifungal, 11,12 antiviral, anti-HIV, antineoplastic, 7 α 2 c antagonists, 13 anesthetics, 14 anti-inflammatory, 15,16 hypotensive, 17 antituberculosis 18 and analgesic agent. 19 Moreover, piperidine complexes represent one of the most ubiquitous heterocyclic moieties existing in food and drug administration (FDA-approved drugs) (Fig.…”
Section: Introductionmentioning
confidence: 99%